Determination of the optimal feed ration for best growth of Hoplobatrachus occipitalis (Günther, 1858) tadpoles reared in controlled medium - GODOME, Théophile; TOSSAVI, COMLAN EPHREM; OUATTARA, Nahoua Issa; FIOGBE, EMILE DIDIER (My University, 2018)
The experiment was carried out for 24 days in open circuit made of 18 cemented ponds containing 50 L water each. The current study aims to estimate the optimal feed ration in Hoplobatrachus occipitalis tadpoles (0.097 ± 0.026 g). Six rations (5, 10, 15, 20, 25 and 30% of biomass/day) were tested in triplicate to evaluate their effect on the growth, survival and the carcass composition of these latter. Results showed Specific Growth Rate and Feed Efficiency was not significantly influenced by feed ration (P˃0.05). Highest Specific Growth Rates were observed in tadpoles fed on rations of 15 and 20 % of biomass or 9.059 ± 0.209 %/Day and 9.027±0.142 %/Day respectively. Besides, highest mean values of Feed Efficiency were obtained in tadpoles fed on rations of 10 and 15% of biomass or 0.778±0.383 and 0.757±0.052. Optimal and maximum feed rations in tadpoles of H. occipitalis are respectively 6.02 and 21.37 % of biomass per day.
Keywords: Hoplobatrachus occipitalis; tadpoles; optimal feed ration